Urban development and waste management planning in Kabul New City, Afghanistan: a case study - Wafa, Wafaurahman; Sharaai, Amir Hamzah; Mukhtar, Sifatullah; Sahak, Kawoon; Afghan, Fazal Rahman (Malaysian Institute Of Planners, 2023)
The municipal solid waste collection system and services of existing Kabul City are not acceptable socially, economically, and environmentally. This study was carried out in 2020“2021 for the Phase-1 area of Kabul New City (KNC). The study aims to analyze different MSWCSS for the KNC area and choose the best option during the planning stage. The average incremental cost for different collection systems was determined, and the results show that the total annualized cost (AN) of the proposed waste collection system (PWCS) is 855.3699 AFN/tonne, while the total operation and maintenance cost (OP) is 577.1235 AFN/tonne. The AN and OP of the stand-alone underground waste collection system (SAUWCS), tailored collection point system, traditional (prevailed) system, and alley waste collection system (AWCS) are 911.3032 AFN/tonne and 499.9017AFN/tonne, 1,681.762 AFN/tonne and 1,267.28 AFN/tonne, 308.9254 AFN/tonne and 186.3363 AFN/tonne, and 716.7706 AFN/tonne and 410.5375 AFN/tonne, respectively. The social and environmental analysis for the PWCS, SAUWCS, existing system, and AWCS obtained scores of 19, 29, -6, 17, and -5, respectively. From the cost-benefit analysis, it has been proposed that for the PWCS of low-rise residential areas, three wheelie bins of different colors will be provided to each housing unit. The total costs per tonne of solid waste for the PWCS, SAUWCS, TCPS, and traditional system are 2,832.1952, 3,638.137205, 3,888.6272, 751.45984, and 1,975.8152, respectively. For the PWCS of residential areas, chute waste collection systems are planned for high-rise apartment buildings and SAUWCSs are planned in commercial areas.